Genetic and morphometric comparison of two isolated populations of Barilius bendelisis (Cypriniformes: Cyprinidae) from the Indian Himalayas - Kumar, Sumit (2019)
Barilius bendelisis (Hamilton) inhabits cold water drainages of the Himalayan region, occurring near the stream banks. It is an important component of the diet of rural population of Uttarakhand and Jammu. Despite the aquaculture importance of B. bendelisis, no extensive molecular characterization from two geographically isolated rivers, Alaknanda and Chenab, has been conducted. In order to study those aspects, 567 samples of B. bendelisis were analysed and collected from these tributaries of two geographically isolated rivers between March of 2015 and April 2017. The morphometric data were analysed by means of truss analysis using tpsDig2 and PAST, whereas the genetic characterization was performed using the COI gene. In truss analysis 14 landmarks resulting in 90 measurements were studied from the digitized images of the sampled specimens. In total 23 measurements exhibited significant differences among the populations of B. bendelisis. The principal component analysis (PCA) generated seven components explaining- 93.15 % of total variance. Discriminant function analysis (DFA) revealed that 83.8 % of the specimens were classified into their original populations. Truss based morphometry and Maximum likelihood type of phylogenetic tree revealed heterogenicity between the two geographically isolated populations of B. bendelisis.